Numerical and Experimental Analysis of Photovoltaic-Integrated Energy Storage System for Electric Vehicle Fast Charging - Furkan Dincer; Emre Ozer (IEEE Access)
Electric vehicles (EVs) have emerged as a pivotal technology for environmental protection, driving the development of battery energy storage systems (BESS) for sustainable charging solutions in smart cities. This paper investigates the implementation of BESS in smart cities to facilitate the charging of EVs, with the aim of improving air quality and promoting sustainable practices. The proposed model involves the selection of seven distinct EV models, each with varying battery capacities and ranges. The model has been developed further by the addition of an annual travel scenario, in which EVs are assumed to be used for daily commuting activities, such as work, school and travel based on family usage profiles. Charging EVs is facilitated by DC fast-charging units, with the charging stations themselves being equipped with BESS capable of charging up to 70 EVs on a daily basis. Proposed BESS is connected to a grid that utilizes electricity generated by a solar power plant (SPP). The SPP has been experimentally designed to generate sufficient electricity to power 10 charging points, with a capacity of up to 700 EVs per day. Thus, a single SPP installation is capable of supplying the entire network of 10 fast-charging stations deployed across the city. Furthermore, a detailed assessment of different state of charge analysis (95–70%) shows a trade-off between battery life and flexibility. The system is economically viable (8.06 years payback) and enables up to 1,518 tons/year CO2 reduction.